Pengaruh Kepemimpinan Transformasional dan Komunikasi Organisasi terhadap Kinerja Anggota Kepolisian Sektor Sejajaran Polres Solok dengan Disiplin sebagai Variabel Moderasi - Barata Rahmat Sukarsih; Eka Risma Putri (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2026)
This study is motivated by the importance of improving the performance of police officers as the frontline of public service, which is influenced by transformational leadership, organizational communication, and work discipline. In practice, variations in officer performance are still observed at police precincts under the Solok Police Department, as evidenced by differences in case resolution rates, service responsiveness, and the effectiveness of task execution. These conditions are suspected to be related to the suboptimal implementation of transformational leadership, organizational communication, and work discipline among officers. This study aims to analyze the influence of transformational leadership and organizational communication on police officer performance, as well as to test the role of work discipline as a moderating variable. The research method used is a quantitative approach with a field research design. The study population consisted of all 126 members of the police stations under the Solok Police Department, with a sample size of 124 respondents. Data collection was conducted by distributing questionnaires to police officers, which were then analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The results of the study indicate that transformational leadership has a positive and significant effect on member performance, with a coefficient of 0.754, a T-statistic of 3.550 (>1.96), and a P-value of 0.000 (<0.05); thus, the first hypothesis is accepted. Organizational communication has a negative and significant effect on performance with a coefficient of -0.615, a T-statistic of 2.509 (>1.96), and a P-value of 0.012 (<0.05). Work discipline does not moderate the effects of transformational leadership or organizational communication on performance, as both show insignificant results. In conclusion, improved police officer performance can be achieved through the implementation of effective transformational leadership and the strengthening of organizational communication.